Pengaruh Percaya Diri Siswa dan Kemampuan Komunikasi Terhadap Pembelajaran di Sekolah MI An-Nisa - Syatriadin Syatriadin (AL-FURQAN, 2021)
Educational communication is a process of interaction in learning activities, where students can convey ideas both orally and in writing which includes reading, listening, discussion, explaining, writing, interpreting, and evaluating ideas, symbols, terms, and information. Apart from that, the symbol of self-confidence is the most important basic asset in a person to be able to actualize himself. Judging from the process, education is one part of communication and as a process involving two components consisting of humans, namely teachers as communicators and students as communicants. A common reason people join small groups is to learn from others. In general, education takes place in a planned way in the classroom face to face (face to face), because the groups are small and there is communication in the form of group communication but at any time it can turn into interpersonal communication. Based on several descriptions of self-confidence, it can be concluded that self-confidence is a belief and attitude that students have about their abilities and can develop and cultivate themselves in overcoming various kinds of problems, both positive and negative. Likewise, with communication here, it can be concluded that this communication is a process of interaction in learning activities, where later students can convey ideas to one another by reading, listening, and writing